Tungstophosphoric acid supported on zirconia: A recyclable catalyst for the green synthesis on quinoxaline derivatives under solvent-free conditions - Sosa, Alexis Alberto (2013)
A green, simple, and fast procedure has been developed for the preparation of quinoxaline derivatives by a condensation of 1,2-diamines with 1,2-dicarbonyl compounds in the presence of zirconium oxide modified with tungstophosphoric acid (H3PW12O40) as a heterogeneous catalyst, in a solvent-free medium using conventional heating. Quinoxaline derivatives were formed in short-time periods and excellent yields (65 and 100%). The reaction work-up is very simple and the catalyst can be easily separated from the reaction mixture and reused several times in subsequent reactions without appreciable loss of the catalytic activity.